EVALUASI IMPLEMENTASI PRINSIP TRANSPARANSI DAN AKUNTABILITAS PADA BADAN LAYANAN UMUM DAERAH PENDIDIKAN (Studi Kasus : SMK Negeri Mandiri ‘X’ Jakarta) - Alwahdy, Fadly; Setyaningrum, Dyah (Jurnal Apresiasi Ekonomi, 2023)
The establishment of the Regional Public Service Agency (BLUD) SMK in DKI Jakarta Province was carried out as part of the Regional Strategic Activities (KSD) Revitalization of Vocational High Schools (SMK) program, which aims to improve the quality and competitiveness of Indonesian human resources. However, the implementation of BLUD SMK faces challenges in optimizing the sales results of the production unit, achieving performance targets, and the availability of competent human resources. This study aims to analyze the challenges of implementing the principles of transparency and accountability in accordance with Good School Governance at BLUD SMK Mandiri 'X' Jakarta. This research uses a case study research method. The type of data used is primary data obtained directly from informants through in-depth interviews. The analysis results show that there are operational problems that have not been fully resolved, such as the absence of updating the service rates of SMK production units stipulated in the Governor's Regulation of DKI Jakarta Province. Additionally, newly established BLUD SMKs do not yet have a tariff gubernatorial regulation that serves as the basis for determining the selling price of the products/services offered.